2008
DOI: 10.1017/s1138741600004327
|View full text |Cite
|
Sign up to set email alerts
|

Psychology of Male and Female Communicative Activity

Abstract: The article features a brief overview of theoretical and empirical studies in communication psychology and sociability of men and women, boys and girls. Russian and foreign studies are summarized to point out that girls and women place greater emphasis on communication and interpersonal relations than do boys and men. Moreover, female communication is more emotional. The article presents the results of the author's own empirical study of male and female communicative activity. Communicative activity is viewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
0
8
0
4
Order By: Relevance
“…Furthermore, Trudgill (1985) says that males' and females' speeches are not only different; and females' are also better than males'. Vasyura (2008) points out that male are more confident in communicative activity. In addition, O'Brien (1991) revealed distinctive differences in cognitive styles between males and females as well as systematic differences associated with major area of study, level of academic achievement, and educational level.…”
Section: Learning Styles Gender and Subject Preferencementioning
confidence: 99%
“…Furthermore, Trudgill (1985) says that males' and females' speeches are not only different; and females' are also better than males'. Vasyura (2008) points out that male are more confident in communicative activity. In addition, O'Brien (1991) revealed distinctive differences in cognitive styles between males and females as well as systematic differences associated with major area of study, level of academic achievement, and educational level.…”
Section: Learning Styles Gender and Subject Preferencementioning
confidence: 99%
“…As children become adolescents and then adults, their perceptions of gender norms are shaped by the gender-normative communication they experience. It was found that during adolescence, gender-conditioned behavior was most prominent, with boys fitting practical expression stereotypes and girls fitting the expressive emotion stereotype (Vasyura, 2008). However, to some degree, older members of society also support the same gender stereotypes, but to a less extent.…”
Section: Vasyuramentioning
confidence: 99%
“…The students' individual psychological attributes were determined via another series of tests meant to determine characteristics of their nervous system, their psychodynamic characteristics, their personality, gender characteristics, as well as socio-psychological characteristics. A final test determined each individual's perception of a difficult communication partner for both genders (Vasyura, 2008).…”
Section: Vasyuramentioning
confidence: 99%
“…Soon after my first 8-scale Structure of Temperament Questionnaire (STQ) was published and was adopted in the West [25][26][27][28][29][30][31], I started working on an upgrade of this model to include 4 more scales describing intellectual aspects of behaviour. This research resulted in the Extended STQ [2,[32][33][34][35][36]. Irina Trofimova and I call this the 'activity-specific approach' in temperament research, as it separates between aspects of behaviour related to specific types of activities-physical, social-verbal and mental.…”
Section: Activity-specific Approach In Temperament Researchmentioning
confidence: 99%